Por cima das fronteiras : o caso de Jorge [de] Montemor - Fardilha, Luís de Sá (2014)
Jorge de Montemor's choice for Castilian as a literary language, apart from other explanations that have to do with biographical circumstances, may translate a deliberate position in favour of a certain type of cultural Iberism: using a lingua franca to promote the dissemination of authors and works written in the different Iberian languages outside their specific and natural linguistic regions, to facilitate full cultural integration.